Propriedades funcionais tecnológicas de concentrado proteico obtido a partir de amêndoa de castanha de caju (Anacardium occidentale L.) - Rocha, Neilane Gomes da (2023)
The cashew nut kernel stands out as the main product of cashew culture. However, in the processing of this kernel a high percentage is broken, making it of lower market value. Thus, various technological alternatives have been studied to produce new products from these lower-value materials, including oil. Processing the oil, obtained by pressing the kernels, produces a co-product - called Partially Defatted Cake (PDC) - which has the potential to be used as a raw material for producing protein products. The aim of this work was to evaluate the protein concentrate obtained from PDC to establish its potential as an ingredient in the food industry. To this end, the centesimal composition of PDC was evaluated. After concentrating the protein, the techno-functional properties, mineral profile, toxicity, phenolic compounds and antioxidant activity of the cashew nut kernel protein concentrate were analyzed. In addition, a sensory evaluation was conducted, comparing it with the main products available on the market (rice, pea and soy protein concentrates). The results showed that the PDC, after the concentration stage, had a protein content of 27% and the protein concentrate reached a protein concentration of 57.96%. The cashew nut kernel protein concentrate, as a plant-based product, has significant nutritional characteristics, such as high protein content, significant results in terms of techno-functional properties, showing its potential for foods that require emulsifying activity and stability, water and oil absorption capacity, gel formation and solubility. The protein concentrate proved to be a source of minerals, especially phosphorus. As well as being a product with no toxicity observed, it also showed phenolic compounds and antioxidant activity. Evaluating the sensory attributes of appearance, aroma and overall impression, it was found that the cashew nut kernel protein concentrate showed positive results and was even better than the other protein concentrates evaluated and available on the market. The cashew nut kernel protein concentrate has attributes that allow it to be used as an enriching and innovative ingredient, with nutritional characteristics and techno-functional properties for different applications of interest to the food industry.